An investigation of the distribution and transfer of Traditional Ecological Knowledge based on generation, gender and resource use - Agbemenya, Seyram Awushie (My University, 2011)
The state of Traditional Ecological Knowledge (TEK) is of importance to ecologists and conservationists considering the recent trends in the loss of local culture and indigenous knowledge systems worldwide. An understanding of the factors that affect the distribution and transmission of TEK may offer scientists an insight into how it can be conserved to persist to inform ecological decisions. This study investigated the distribution and transmission of TEK based on gender, age and tree resource use in two rural communities in the Mpumalanga Province of South Africa. The distribution of this knowledge was assessed based on respondents’ ability to identify local tree species, their uses and conservation techniques. Their ecological knowledge of a number of common and rare indigenous tree species was also assessed. This was done mainly through focus group discussions, individual interviews and a participatory appraisal technique. Age group rather than gender had a significant effect on the distribution of TEK with old age respondents being more knowledgeable than youths and middle aged respondents. Resource use also affected the distribution of knowledge indicating that knowledge was highly dependent on resource use. Females were the main actors in the transfer of TEK in this community and majority of this knowledge was acquired through passive means. The results revealed a combination of factors that may pose a threat to the loss of TEK in these communities. These factors include; the continuous and unregulated harvesting of trees in the area, the effects of modernisation and globalization on aspects of the traditional community and the high levels of rural urban-migration.
Keywords: Traditional Ecological Knowledge; knowledge transfer; knowledge distribution; natural resource use; modernisation